Perceptions of the students and the teachers towards the use of code switching in EFL classrooms - Merve Karakaya; Kenan Dikilitaş (Literacy Trek, 2020)
The purpose of this study is to shed light on the perceptions of the teachers and the students towards the use of code switching in EFL classrooms where English was a medium of instruction. Besides, it mentioned the functions of code switching in the learning and teaching environment. The research was taken place at three state universities in the western part of Turkey and the participants of the students were volunteer university students (N=550) diversified according to their gender, English proficiency level, English learning year, and age. Moreover, English instructors (N=50) who volunteered to participate in the study and the participants varied depending on their gender, nationality, and teaching experience. Questionnaires were distributed to the students for the quantitative part of the research and analyzed by CHIAD analysis as well as descriptive analysis. Interview questions were asked to the teachers and the answers were investigated for the qualitative part of the research and teachers recorded semi-structured interview responses were processed deductively. The results are discussed, and some suggestions are given with respect to the present literature.